2021
DOI: 10.3346/jkms.2021.36.e44
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Outbreak on Trends in Emergency Department Utilization in Children: a Multicenter Retrospective Observational Study in Seoul Metropolitan Area, Korea

Abstract: Background Understanding the changes in emergency department (ED) visit patterns during the coronavirus disease 2019 (COVID-19) outbreak is important for effectively operating EDs during the pandemic. We aimed to analyze the changes in pediatric ED visits during the COVID-19 pandemic and examine the relationship between the number of ED visits and the stringency of government social distancing measures. Methods This multicenter retrospective study used data of pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 15 publications
6
45
2
2
Order By: Relevance
“…In addition, the incidence of influenza virus, respiratory syncytial virus, and mycoplasma infections, which are prevalent in every winter, also decreased in 2020. 4 5 6 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the incidence of influenza virus, respiratory syncytial virus, and mycoplasma infections, which are prevalent in every winter, also decreased in 2020. 4 5 6 …”
Section: Introductionmentioning
confidence: 99%
“…21-23 Therefore, the reduction of the door-to-balloon time could be attributed to decreased emergency care utilisation during the early COVID-19 pandemic as patients with low severity defer emergency department visits owing to the fear of the infection in the medical facility. 22 23 This decrease in emergency care utilisation was also observed during the MERS outbreak in 2015 in South Korea. 24…”
Section: Discussionmentioning
confidence: 55%
“…Previous Korean studies reported decreased number of patient-visit to emergency department (46%-77%) during the early COVID-19 pandemic. [21][22][23] Therefore, the reduction of the door-to-balloon time could be attributed to decreased . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that the number of overall visits to the ED of a Korean tertiary hospital sharply decreased during the COVID-19 pandemic. This decrease has been experienced in many countries according to the studies during the pandemic 11,12) . Despite the decrease in overall visits, higher severity and hospitalization rates were shown in an analysis of all children who visited a U.S. ED over a 10-week period at the beginning of the pandemic 13) .…”
Section: Discussionmentioning
confidence: 98%